PENEGAKAN PERATURAN DISIPLIN PEGAWAI NEGERI SIPIL DI PEMERINTAHAN KABUPATEN KULONPROGO DALAM MENINGKATKAN DISIPLIN KERJA - , LIDWINA APRILLIANA ALLO TANGKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The smooth implementation of governance and national development depends on the perfection of the Civil Service. High discipline is one element to be perfect servants. But in fact, there are many civil servants are often violated. In an effort to improve the discipline of the Civil government has issued a policy that with the enactment of the Government of the Republic of Indonesia Number 53 Year 2010 on Civil Service Discipline Regulations. Accordingly, this study examines how regulatory enforcement Civil Service Discipline in Kulon Progo Regency Government, what are the factors that hinder the enforcement of the Civil Service Disciplinary Code in Kulon Progo Regency Government, and any efforts made to prevent the occurrence of violations of disciplinary rules Civil Servants in Kulon Progo Regency Government. By using the method of empirical legal research, it can be concluded after the enforcement of the penalty is given, a decline in the level of a violation, because the enforced regulations cause offense becomes lower, and labor discipline positively influence the performance of civil servants in the Government District of BKD is faced Kulon progo. Barriers faced by limitations discipline personnel in monitoring the Civil Service, Psychological barriers in the form of a good relationship between leaders and subordinates, leaders on education still do not understand the rules, and weak supervision of the respective chairman on education. Efforts made by Regional Employment Board Kulon Progo Regency to prevent offenses committed by Goverment civil servants in Kulon Progo Regency Government is to provide socialization of the norm of regulating the discipline of civil servants is Government Regulation Number 53 Year 2010 concerning discipline of civil servants, doing the inspection (unannounced) to government agencies Kulon Progo Regency, and provide rewards and Punishment to the Goverment Civil Servant. Based on these results, the authors recommend a few things: 1) it is expected that the Civil Service to better understand and know about Goverment Civil Servants Discipline Regulations, 2) Development and continuous monitoring should be carried out and developed by Regional Employment Board, 3) should be held socialization or legal seminar on Government Regulation Number. 53 Year 2010 on Civil Service Discipline, especially regarding the obligations and prohibitions Goverment Civil Servants. Keywords: Goverment Civil Servant, Goverment Civil Servant Discipline Regulations, Disciplinary Penalties and Discipline Work